Synthesis of polystyrene of reduced flammability by suspension polymerization in the presence of halogen-free additives - Jankowski, P.; Kędzierski, M. (Polimery, 2011)
A method for the synthesis of polystyrene of reduced flammability by suspension polymerization in the presence of organic phosphor compounds or their compositions with organically modified layered aluminosilicates of the montmorillonite type has been developed. The additives or their compositions were introduced into the polystyrene during suspension polymerization by applying such procedures as to minimize their effects on the process. Polystyrenes of reduced flammability up to maximal vertical and horizontal burning rate categories of V-1 and FH-1, respectively, and of an oxygen index in the 21-26 % range were obtained.